Reproductive and sexual health knowledge, experiences, and milestones in young adults with life-long HIV. Issue 3 (3rd March 2020) - Aepfelbacher, Julia A.; Chaudhury, Chloe S.; Mee, Thomas; Purdy, Julia B.; Hawkins, Karyn; Curl, Kara-anne; Dee, Nicola; Hadigan, Colleen
ABSTRACT: Reproductive and sexual health outcomes of adults with perinatal human immunodeficiency virus (PHIV) have not been well-characterized. This prospective cross-sectional study of 35 adult persons living with HIV (PLWH) from early life and 20 matched HIV-negative controls assessed quality of life, depressive symptoms, HIV transmission knowledge, and sexual/reproductive behaviors through self-report questionnaires. PLWH scored significantly worse than controls on depressive symptoms ( p  = 0.04) and two of six quality of life domains ( p  = 0.03, p  = 0.0002). In contrast, PLWH scored significantly higher on transmission knowledge in the context of family planning ( p  = 0.002). PLWH were more likely to learn about sex from healthcare providers ( p  = 0.002) and were more confident in their sexual/reproductive health knowledge ( p  < 0.05). Both groups reported inconsistent condom use, but PLWH were more likely to have planned pregnancies ( p  = 0.005) and to share pregnancy planning with their partners ( p  < 0.05). Despite the challenges of living with a chronic stigmatized condition, adults with PHIV were knowledgeable about HIV transmission and family planning and demonstrated sexual practices and reproductive outcomes similar to age-matched controls. However, sub-optimal rates of viral suppression, inconsistent condom use, and the psychosocial impact of living with HIV continue to require the attention of healthcare provides for young adults with PHIV.